Using a common commensal bacterium in endangered Takahe as a model to explore pathogen dynamics in isolated wildlife populations. Issue 5 (11th May 2015) - Grange, Zoe L.; Gartrell, Brett D.; Biggs, Patrick J.; Nelson, Nicola J.; Marshall, Jonathan C.; Howe, Laryssa; Balm, Matthew G.M.; French, Nigel P.
Abstract Predicting and preventing outbreaks of infectious disease in endangered wildlife is problematic without an understanding of the biotic and abiotic factors that influence pathogen transmission and the genetic variation of microorganisms within and between these highly modified host communities. We used a common commensal bacterium, Campylobacter spp., in endangered Takahe (Porphyrio hochstetteri) populations to develop a model with which to study pathogen dynamics in isolated wildlife populations connected through ongoing translocations. Takahe are endemic to New Zealand, where their total population is approximately 230 individuals. Takahe were translocated from a single remnant wild population to multiple offshore and mainland reserves. Several fragmented subpopulations are maintained and connected through regular translocations. We tested 118 Takahe from 8 locations for fecal Campylobacter spp. via culture and DNA extraction and used PCR for species assignment. Factors relating to population connectivity and host life history were explored using multivariate analytical methods to determine associations between host variables and bacterial prevalence. The apparent prevalence of Campylobacter spp. in Takahe was 99%, one of the highest reported in avian populations. Variation in prevalence was evident among Campylobacter species identified. C. sp. nova 1 (90%) colonized the majority of Takahe tested. Prevalence of C. jejuni (38%) and C. coli (24%) was different between Takahe subpopulations, and this difference was associated with factors related to population management, captivity, rearing environment, and the presence of agricultural practices in the location in which birds were sampled. Modeling results of Campylobacter spp. in Takahe metapopulations suggest that anthropogenic management of endangered species within altered environments may have unforeseen effects on microbial exposure, carriage, and disease risk. Translocation of wildlife between locations could have unpredictable consequences including the spread of novel microbes between isolated populations.